Learning and Results in World Bank Operations: Toward a New Learning Strategy - and World Bank (IEG , The World Bank, 2015)
This report is the second in a program of evaluations that the Independent Evaluation Group (IEG) is conducting on the learning that takes place through World Bank projects. Learning and knowledge are treated as parts of a whole and are presumed to be mutually reinforcing.
Keywords: IMPORTANT